Old People Are Still Doing It! - Ní Lochlainn, Mary (Trinity Student Medical Journal, 2012)
Research suggesting that a high pro- portion of men and women remain sexually active well into later life refutes the prevailing illusion that ageing and sexual dysfunction are unequivocally linked. Age related physiological changes do not render a meaningful sexual relationship im- possible or even necessarily difficult. Many of these physiological changes are modifiable. There are various therapeutic options available to pa- tients to achieve maximum sexual capacity in old age. In this article I review the physiologi- cal sex-related changes that occur as part of the normal ageing process in men and women. I address the effect of illness on sexual function. In addi- tion, I will summarise the attitudes and perceptions of the media and general public towards sexual activ- ity and ageing. An understanding of the sexual changes that accompany the ageing process may help general practitioners and other doctors to give practical and useful advice on sexuality as well as refute the mis- conception that ageing equates to celibacy. A thorough awareness of this aspect of older people’s quality of life can raise meaningful expecta- tions for ageing patients.